Cyclodextrins’ Internal Cavity Hydration: Insights from Theory and Experiment - Silvia Angelova; Stiliyana Pereva; Todor Dudev; Tony Spassov (Inorganics)
In this short review, recent findings from both theory and experiment regarding the process of hydration of α-, β-, and γ-cyclodextrins are summarized and critically assessed. Key important questions are addressed, including: What factors govern the number of water molecules entrapped in the internal cavity of the host macrocycle? What is the driving force behind this process? What are the “hot spots” for water entrapment inside the host cavity? What is the underlying mechanism of water hydration and dehydration of cyclodextrins? What is the role of the confined water cluster in determining the outcome of the host–guest complexation between cyclodextrins and molecules of inorganic/organic nature? To what extent does water hydration affect the crystalline structure of the cavitand?